Developing a new framework of English lexical and morphological development among Malaysian primary- school children - Mohamed Salleh, Rabiah Tul Adawiyah (2020)
It is an incontrovertible fact that English is currently the lingua franca of the world. Increasing globalisation has made it crucial to raise the standards of English proficiency among youth in Malaysia. In fact, there have been many reports on the deteriorating standards of English among young Malaysians. Regardless of the many reforms taken by the government as corrective measures to improve Malaysian students’ English proficiency, we have yet to see any positive outcome. Most studies investigating the issue of Malaysian students’ proficiency have focused primarily on the policies of the education system, the pedagogy, and the teacher’s perspective. Studies to document the English acquisitional trajectory of Malaysian learners are scant and this normative data is imperative for syllabus-designers, policy-makers, teachers as well as linguists to create English materials that are suitable and effective for learning. Thus, this research proposes to investigate the development of lexicon (vocabulary) and morphology (grammar) in Malaysian primary-school children. Our focus will be on the students’ speech, particularly examining how English lexicon and grammar develop among these children in one year. These children attend a primary school that is based on the national education curriculum (KSSR). They will be recorded four times at three monthly intervals in the study. Other than their English development, the student’s home factor will also be examined. The outcome of this study will help us develop a framework for English language acquisition that will enable teachers and syllabus designers to create materials that will help learners to acquire and improve English proficiency.